Dalbavancin in clinical practice in Spain: a 2 year retrospective study. Issue 6 (22nd December 2022) - Morata, Laura; Aguado, José María; Salavert, Miguel; Pasquau, Juan; Míguez, Enrique; Muñoz, Patricia; Rosselló, Irantzu; Almirante, Benito
Abstract: Objectives: Dalbavancin is approved for the treatment of acute bacterial skin and skin-structure infections (ABSSSIs) in adults. Its unique pharmacokinetic properties allow daily dosing to be avoided. The objective was to describe the sociodemographic and clinical characteristics of patients treated with dalbavancin in Spain, and to evaluate its effectiveness and safety in real-world settings. Patients and methods: This non-interventional, retrospective, observational and multicentre study included patients who received at least one dose between 2018 and 2019 in seven Spanish hospitals. Results: In total, 187 patients were included. The most common comorbidities were cardiovascular disease (27.4%) and diabetes mellitus (23.5%). Dalbavancin was used to treat osteoarticular infections (28.3%), ABSSSIs (22.5%), cardiovascular infections (20.9%) and catheter-related infections (18.2%). The most prevalent pathogens were Staphylococcus aureus (34.2%), CoNS (32.6%), and enterococci (12.8%). The main reason for use was early hospital discharge (65.8%). Most patients were treated with 1500 mg in a single dose (35.3%) and the median duration of treatment was 2 weeks. The treatment was clinically successful in 91.4% of cases. Six patients (3.2%) reported adverse events. Physicians agreed on the potential reduction of hospitalization days (85.3%). A subanalysis of patient characteristics and type of pathogen showed similar results in terms of efficacy and safety. Conclusions: Dalbavancin seems to be effective and safe as second-line treatment in severe Gram-positive infections. It improves treatment adherence and allows outpatient management. Furthermore, the effectiveness and safety profile are maintained against diverse microorganisms in Gram-positive infections and regardless of the patients' comorbidities at baseline, or age.